PENGARUH NEGARA DAN ORGANISASI KEAGAMAAN PADA KEBIJAKAN SEKOLAH BERBASIS AGAMA - Yusuf, Mohamad; Sterkens, Carl (Masyarakat Indonesia, 2013)
This paper describes different models of religious education that have been adopted by Islamic, Christian and Hindu schools in Indonesia. We describe the educational goals, teaching methods and curriculum content, as well as the opinions of teachers and headmasters concerning religious education. Moreover, we examine the institutional influence of State and religious communities on religious education in these schools. We selected three areas in which, respectively, Muslims, Christians and Hindus were in the majority. In each area, we selected five secondary schools (Sekolah Menengah Atas or SMA): three schools representing the majority group in the concerning area, and two schools belonging to religious minority groups. We interviewed fifteen headmasters and nineteen teachers of religion. We found that most religiously affiliated schools employ a mono-religious model of religious education. Even though some schools introduce teachings about other religions in their curriculum, the perspective is from their own point of view. The Catholic school in West Java (Christian minority) offers an inter-religious model of religious education. Moreover, we discovered that the State and religious communities influence the policies of religious education at school level in different ways. In Islamic schools, all types of institutional power from both the State and religious communities are responded positively. In Christian schools the influence of the State is less strong than in Islamic schools. In Hindu schools the State’s regulations are very influential on the policies of religious education.